Gut Microbiota Interplay With COVID-19 Reveals Links to Host Lipid Metabolism Among Middle Eastern Populations - Al Bataineh, Mohammad Tahseen; Henschel, Andreas; Mousa, Mira; Daou, Marianne; Waasia, Fathimathuz; Kannout, Hussein; Khalili, Mariam; Kayasseh, Mohd Azzam; Alkhajeh, Abdulmajeed; Uddin, Maimunah; Alkaabi, Nawal; Tay, Guan K.; et al. (Frontiers in Microbiology, 2021)
The interplay between the compositional changes in the gastrointestinal microbiome, SARS-CoV-2 susceptibility and severity, and host functions is complex and yet to be fully understood. This study performed 16S rRNA gene-based microbial profiling of 143 subjects. We observed structural and compositional alterations in the gut microbiota of the SARS-CoV-2 infected group in comparison to non-infected controls. The gut microbiota composition of the SARS-CoV-2 infected individuals showed an increase in anti-inflammatory bacteria such as Faecalibacterium (p-value=1.72x10-6) and Bacteroides (p-value=5.67x10-8). We also revealed a higher relative abundance of the highly beneficial butyrate-producers such as Anaerostipes (p-value= 1.75x10-230), Lachnospiraceae (p-value= 7.14x10-65), and Blautia (p-value= 9.22x10-18) among the SARS‑CoV‑2 infected group in comparison to their control group. Moreover, PICRUSt functional prediction analysis of the 16S rRNA gene abundance data showed substantial differences in the enrichment of metabolic pathways such as lipid, amino acid, carbohydrate, and xenobiotic metabolism, among others in comparison between both groups. We discovered an enrichment of linoleic acid, ether lipid, glycerolipid, and glycerophospholipid metabolism among the SARS-CoV-2 infected group, suggesting a link to SARS-CoV-2 entry and replication in host cells. We estimate the major contributing genera to those four pathways: Parabacteroides, Streptococcus, Dorea, and Blautia, respectively. The identified differences provide a new insight to enrich our understanding of SARS-CoV-2-related changes in gut microbiota, their metabolic capabilities, and potential screening biomarkers linked to COVID-19 disease severity.